Implementing Polya’s Problem-Solving Framework to Improve Word Problem Solving in Secondary School Mathematics - Yuwono, Timbul; Verawati, Petronela; Wahyuni, Tri (Universitas Sultan Ageng Tirtayasa, 2025)
Abstract: This study explores the effectiveness of the Polya Problem Solving Method in improving students' ability to solve word problems in mathematics at SMPN 17 Malang, Indonesia. The main objective is to determine whether this method can improve students' problem-solving abilities in the context of a linear equation system with two variables. A Classroom Action Research (CAR) approach is used, with two implementation cycles. Data was collected through pre- and post-test tests, classroom observations, and student interviews. These findings show a significant improvement in student performance, with the percentage of students meeting the Minimum Completeness Criteria (MCC) increasing from 36.3% in the pre-test to 84.84% after Cycle II. In addition, student engagement and teacher effectiveness increased markedly, especially in the second cycle, highlighting the importance of personalized support and active learning strategies. The results show that the Polya method can be very effective in fostering critical thinking and problem-solving skills in mathematics. This study contributes to the existing literature by demonstrating the benefits of structured problem-solving methods in Indonesian secondary education. Further research is recommended to explore the long-term effects of this method and its application in different educational contexts.